Practice affairs committee. (1st June 2004) - Sadowski, Dan
Abstract : The Practice Affairs Committee has had a productive year representing the interests of gastroenterologists involved in clinical care. The principle mandate of the committee is to address all issues relevant to the practice of gastroenterology, such as participation in the development of clinical practice guidelines and education programs, and the facilitation of clinical research. A major activity in 2003 was participation in the drafting of several new clinical practice guidelines: Infliximab and the management of Crohn's disease; Screening for colorectal cancer; and Management of gastroesophageal reflux disease.